Changes in Students' Maladaptive Behavior through Cakna Pilgrimage Program: Perubahan Perilaku Maladaptif Siswa Melalui Program Ziarah Cakna - Tara, Atasyah Tara Aneldi; alfin, Alfin Siregar (Indonesian Journal of Innovation Studies, 2025)
General Background: Maladaptive behaviors in students, particularly internalizing types such as withdrawal and emotional distress, are prevalent in primary schools and can hinder both academic achievement and social development. Specific Background: In Malaysia, the Ministry of Education introduced the Ziarah Cakna (home visit) program as a holistic intervention to strengthen school-family partnerships in addressing such issues. Knowledge Gap: While home visit strategies are documented in broader educational contexts, empirical studies exploring their specific role in reducing internalizing maladaptive behaviors at the primary school level remain scarce. Aims: This study investigates the effectiveness of Ziarah Cakna in modifying maladaptive behaviors among students at SK Bandar Puteri Jaya, Sungai Petani, Kedah. Results: Using a qualitative phenomenological method, findings reveal significant behavioral improvements among participants, including increased emotional stability, better attendance, and enhanced social interaction, resulting from collaborative efforts among teachers, students, and families. Novelty: This study offers a contextualized examination of Ziarah Cakna as a culturally embedded intervention, highlighting its integrative and empathetic approach. Implications: The findings provide practical insights for school counselors and policymakers, suggesting that empathetic, home-based interventions can serve as effective strategies to support students’ emotional and behavioral well-being.Highlight : The study highlights the effectiveness of the Ziarah Cakna (Home Visit) program in reducing internalizing maladaptive behaviors among elementary students. It emphasizes collaborative communication between schools and families as a core strategy for behavioral change. The research offers a contextual, empathetic intervention model valuable for guidance and counseling practices in schools. Keywords : Ziarah Cakna; Home Visit; Maladaptive Behavior; Counseling Intervention; Elementary Students